The Non-Linear and Heterogeneous Effects of Inventory Turnover and Liquidity on Profitability: A Panel Quantile Study of Indonesia Firms - Rianti Pratiwi; Agung Suwandaru; Nasya Ananda Putri (Relevance: Journal of Management and Business, 2026)
This study investigates the non-linear and heterogeneous effects of inventory turnover and liquidity on firm profitability in an emerging market context. Using panel data from 79 non-financial firms listed on the Indonesia Stock Exchange (formerly Bursa Efek Jakarta) over the 2021–2024 period, yielding 316 firm-year observations, this research employs fixed effects models and panel quantile regression (Machado & Santos Silva, 2019) to test for inverted U-shaped relationships and distributional heterogeneity. The findings reveal three primary results. First, inventory turnover exhibits a statistically significant inverted U-shaped relationship with return on assets (ROA), with an optimal turnover level of 8.57 times per year (95% CI: 6.92–10.45), confirmed by the Lind and Mehlum (2010) U-test. Second, the effects of inventory turnover are highly heterogeneous across the profitability distribution: the coefficient increases from 0.521 at the 10th quantile (low-profitability firms) to 1.823 at the 90th quantile (high-profitability firms), indicating that high-profitability firms benefit more than three times as much from inventory efficiency improvements. Third, current ratio exhibits positive effects on profitability that also increase across quantiles, from 0.312 to 0.945. Sub-period analysis reveals that the optimal turnover level shifted from 7.89 during the post-pandemic disruption (2021–2022) to 9.12 during the recovery period (2023–2024). These findings contribute to working capital management theory by integrating non-linearity and heterogeneity, provide managers with a concrete inventory turnover benchmark, and demonstrate the value of quantile regression methods in financial research.